Production of bio-oil from fast pyrolysis of biomass using a pilot-scale circulating fluidized bed reactor and its characterization. (15th March 2019) - Park, Jo Yong; Kim, Jae-Kon; Oh, Chang-Ho; Park, Jong-Wook; Kwon, Eilhann E.
Abstract: To circumvent the adverse impacts arising from an excessive use of fossil fuels, bioenergy and chemical production from a carbon neutral resource (biomass) has drawn considerable attention over the last two decades. Among various technical candidates, fast pyrolysis of biomass has been considered as one of the viable technical routes for converting a carbonaceous material (biomass) into biocrude (bio-oil). In these respects, three biomass samples ( i.e ., sawdust, empty fruit bunch, and giant Miscanthus) were chosen as a carbon substrate for the pyrolysis process in this study. A pilot-scale circulating fluidized bed reactor was employed for the pyrolysis work, and biocrude from the fast pyrolysis process at 500 °C were characterized because the maximum yield of biocrude (60 wt% of the original sample mass) was achieved at 500 °C. The physico-chemical properties of biocrude were measured by the international standard/protocol (ASTM D7544 and/or EN 16900 test method) to harness biocrude as bioenergy and an initial feedstock for diverse chemicals. All measurements in this study demonstrated that the heating value, moisture content, and ash contents in biocrude were highly contingent on the type of biomass. Moreover, characterization of biocrude in this study significantly suggested that additional unit operations for char and metal removal must be conducted to meet the fuel standard in terms of biocrude as bioenergy. Highlights: Bio-oil was produced using a pilot-scale circulating fluidized bed reactor. The maximum yield of bio-oil (60%) was obtained at 500 °C. The properties of bio-oil was significantly improved via extraction process.